The production of urban space in the contemporary city and its resulting urban phenomena - Bezerra, Pamela Fernanda Rodrigues; Moraes, Lúcia Maria (Revista Nacional de Gerenciamento de Cidades, 2022)
The article aims to discuss the production and reproduction of urban space, demonstrating how these socio-spatial dynamics occur and that urban phenomena can occur on consolidated land. Contemporary medium-sized cities undergo growing urbanization and among these occurrences generate segregation, a spreading out, gentrification and witness both land and real estate speculation. Most of these occur as a function of capital or with some kind of intervention by it. It seeks to demonstrate how the production of urban space takes place and which agents are involved in it, in addition to looking at what the relationship between them is: namely capitalist social relations and relations of production. Urban land is a product considered a commodity, and this is the object of a struggle between social classes for access to land. Urban space, considered central and endowed with infrastructure, is, in most cases, appropriated by those who have the greatest amount of capital, leaving the lower social strata with less purchasing power to purchase in peripheral areas often with little or no infrastructure. The methodology used was exploratory with a qualitative approach, with reference to authors with scientific mastery of the subject.